AI-Generated News and the Question of Legal Liability: Who Owns the Truth? https://doi.org/10.5281/zenodo.17787339 - Amna Fazail; Dr. Sajid Sultan; Dr Aqsa Iram Shahzadi (Corresponding Author) (`, 2025)
Artificial intelligence is fast becoming part of the journalism industry and has reinvented how news is created, distributed and understood. Generative AI systems have the potential to generate content imitating human reporting and present difficult legal, ethical and epistemic issues. The paper presents conceptual, legal and policy issues surrounding AI-generated journalism and focuses specifically on authorship, liability, intellectual property and the ethics of truth. It suggests the destabilization of the traditional concepts of human agency, copyright and accountability when algorithms are the pseudo-authors and also assesses the new regulatory frameworks that might be applied to make algorithms more transparent, fair and editorially controlled. The paper discusses the conflict between technological advancement and the right to real information of the population by examining the problem of defamation, copyright ownership, the influence of algorithms and misinformation. It is contended in the paper that AI-generated news ownership is not a proprietary issue but more of collective custodianship and thus necessitates legal, ethical and policy interventions that introduce the elements of responsibility, transparency and moral accountability throughout the data-processing and content-generating algorithms. The analysis offers a context through which societies are able to come to terms with the possibilities of an AI-supported journalism efficiency and the long-standing need to remain truthful and accountable. Keywords: AI-generated journalism, Legal liability, Intellectual property, Authorship, Truth and transparency, Algorithmic accountability, Ethical journalism, Misinformation